FIGURE OF SPEECH IN ENGLISH CHILDREN SONG LYRICS - Meriska Yosiana (Asosiasi Dosen Muda Indonesia, 2022)
Figure of speech or Figurative language, which is usually used in poem, prose, song lyrics and other literary works is interesting because it has implied meaning behind the words. The researcher chooses this topic because it is very unique and tricky to know the meaning not only literally, but also non-literally. This research has two aims, they are to find out the figure of speech found in English Children Song Lyrics and to find out the most dominant the figure of speech found in English Children Song Lyrics. This research was conducted by using descriptive qualitative method. In this research, the descriptive qualitative method was used to analyze figures of speech in English Children Song Lyrics. The sources of data in this research were taken from the lyrics of English Children songs. The results of this research are from the 10 English children song lyrics, there are 23 figures of speech which are found in the English children song lyrics. The figures of speech that are found are similes (3 data), metaphors (4 data), personification (9 data), symbols (2 data), and hyperbole (5 data). The most dominant figure of speech found in the English Children Song Lyrics is personification.